Artikel: Keadilan Sosial Divestasi Saham PT. Newmont Nusa Tenggara Barat Pasca Undang-Undang Cipta Kerja - Suherman, Heru Andryana (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
Share divestment policy aims to increase local participation in natural resource management and encourage equal distribution of economic benefits. However, the implementation of this policy often faces challenges. Undang-Undang Cipta Kerja which is known for its spirit of deregulation and ease of investment, brings significant changes in the regulation of share divestment in the mining sector. The research method used is a descriptive qualitative approach with literature review and policy analysis as the main methods. The results of previous research show that there is no loss to society due to overlapping regulations between the center and regions in investment control. The research results show that although Undang-Undang Cipta Kerja providing flexibility in divestment arrangements, social justice challenges remain. The example, limiting the role of local governments in share management and limiting local communities' access to share ownership can increase social inequality. Share divestment is not only an economic tool but also functions as a broader social justice mechanism, in accordance with the principles of sustainable and equitable natural resource management. The principles of Pancasila social justice, especially the fifth principle of social justice for all Indonesian people emphasizes the importance of fair distribution of the nation's wealth for the benefit of all the people. Principles of justice such as national ownership of natural resources, fair distribution of economic benefits for local communities, community empowerment, reduction of dependency, accountable supervision and balance of economic development and environmental conservation.